The Influence of Green Accounting, Corporate Social Responsibility, and Profitability on Company Value Moderated by Good Corporate Governance - Salisa, Meilenia Rahma; Mardiati, Endang; Rahman, Aulia Fuad (The International Journal of Accounting and Business Society, 2024)
Purpose - This study aims to test the Influence of Green Accounting, Corporate Social Responsibility, and Profitability on Company Value moderated by Good Corporate Governance on mining companies listed on the Indonesia Stock Exchange from 2015 to 2021. Design/Methodology/approach—The sample selection method used purposive sampling with several criteria, resulting in 77 samples. In addition, this study used moderated regression analysis and confirmatory factor analysis. Finding - The results of this research indicate that there is a positive effect between  Corporate Social Responsibility and company value,  there is no effect between Green Accounting and profitability on company value, and Good Corporate Governance moderates the relationship between Green Accounting and profitability on company value. Practical implications—This research has practical contributions for investors and company management. Investors and company management are expected to consider the importance of green accounting, CSR, profitability, and corporate governance in increasing company value. Originality/value—This research has implications for academic enrichment. The results of this study contribute to the Stakeholders and Legitimacy Theory because companies must consider the interests of every stakeholder and social norms through green accounting, CSR, profitability, and corporate governance to increase company value. Keywords — Green Accounting, Corporate Social Responsibility, Profitability, Good Corporate Governance, Company Value Paper Type: Quantitative Research